Bone turnover markers (β-CTX, PINP, ALP) in osteoporosis: correlation with bone loss and fracture risk stratification - Wu, Shiqiang; Wang, Liangming; Zhang, Xiaolu; Cai, Liquan; Ke, Qingfeng; Xu, Jie (Frontiers in Endocrinology, 2026)
ObjectiveTo investigate the correlation of β-C-terminal telopeptide of type I collagen (β-CTX), procollagen type I N-terminal propeptide (PINP), alkaline phosphatase (ALP) with bone mineral density (BMD) in patients with osteoporosis and evaluate their predictive value for secondary fracture risk.MethodsA total of 180 osteoporosis patients and 80 healthy controls were enrolled. The osteoporosis group was stratified into fracture and non-fracture cohorts. Correlation of β-CTX, PINP, ALP with BMD at lumbar spine (L1-4) and femoral neck was assessed using Pearson correlation coefficient. Binary logistic regression model was employed to analyze the risk factors associated with secondary fractures in patients with osteoporosis and receiver-operator characteristic (ROC) curve was used for assessing the predictive utility.ResultsOsteoporosis patients exhibited significantly higher β-CTX, PINP, and ALP levels compared to controls (all P < 0.001), alongside lower BMD at both lumbar spine and femoral neck (P < 0.001). Negative correlations were observed between β-CTX, PINP, ALP, and BMD (r = -0.553 to -0.671, P < 0.001). The fracture group (n=83 vs. n=97 non-fracture) revealed elevated β-CTX, PINP, and ALP levels (all P < 0.001). Logistic regression identified β-CTX, PINP, and ALP as independent risk factors. ROC analysis demonstrated strong predictive accuracy for combined β-CTX, PINP, ALP and BMD (AUC = 0.943), outperforming individual parameters.ConclusionElevated β-CTX, PINP, and ALP levels correlate with reduced BMD and independently predict secondary fracture risk in osteoporosis patients. Integrating these biomarkers with BMD enhances fracture risk stratification, supporting their inclusion in clinical risk assessment tool.